Molecular and histopathological features of Cryptosporidium ubiquitum infection in imported chinchillas Chinchilla lanigera in Japan - Kubota, Rie; Matsubara, Katsuki; Tamukai, Kenichi; Ike, Kazunori; Tokiwa, Toshihiro (Parasitology international, 2019)
Long-tailed chinchillas Chinchilla lanigera are popular rodent species kept both in households, where they are hand-raised as pets, and in zoological facilities. From January 2016 to February 2017, 13 juvenile chinchillas from five facilities in Japan were diagnosed with cryptosporidiosis at the animal hospital. Eight of the cases were fatal. All of the animals were imported from the Czech Republic by the same vendor. Histopathological and multilocus sequence analyses using 18S ribosomal RNA, actin, 70-kDa heat shock protein, and 60-kDa glycoprotein genes confirmed Cryptosporidium ubiquitum of subtype XIId as the etiological agent. Multilocus analysis demonstrated the presence of two new sequence types closely related to the C. ubiquitum Xlld strain isolated from a human in the USA. This study indicated that potentially zoonotic Cryptosporidium is widespread and may have caused a high number of deaths among imported juvenile chinchillas.
Keywords: Feces; Zoonotic infection; Emerging infectious disease; genotyp; Cryptosporidium; Zoonoses; činčila; Cryptosporidiosis; Subtype XIId; Genotype; Communicable Diseases, Emerging; Česká republika; zoonózy; Chinchilla; Animals, Domestic; Communicable Diseases, Imported; importované infekce; Czech Republic; objevující se infekční nemoci; protozoální DNA; Japonsko; RNA ribozomální 18S; Multilocus Sequence Typing; hospodářská zvířata; Multilocus sequence analysis; zvířata; feces; fylogeneze; RNA, Ribosomal, 18S; Japan; DNA, Protozoan; multilokusová sekvenční typizace; kryptosporidióza; Phylogeny; Animals